The missing magic - Elliott, Rebecca (New York : Scholastic Inc., 2022)
Unicorn Bo Tinseltail is excited to attend the Big Festival of Magic, a celebration where creatures use their magic to entertain everyone. But when all the magic mysteriously goes missing, Bo and friends must find a way to return the magic to the forest. Can the unicorns save the day without being able to use any magic?
K-3
3.3
590L
Keywords: Unicorns -- Juvenile fiction; Magic -- Juvenile fiction; Lost articles -- Juvenile fiction; Diaries -- Juvenile fiction; Unicorns -- Fiction; Magic -- Fiction; Lost and found possessions -- Fiction; Diaries -- Fiction; Fantasy; Diary fiction; Fantasy fiction